Pemuridan Remaja Kristen di Era Digital: Strategi Kontekstual melalui Pendidikan Agama dan Literasi Iman Bangsa-Bangsa - Chanita Christie (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2025)
In the digital age, Christian youth face increasing challenges in maintaining moral integrity, spiritual growth, and strong identity in Christ. The widespread exposure to negative digital content, particularly pornography, combined with the lack of contextual spiritual guidance, has weakened discipleship among young believers. This study explores a contextual strategy for Christian youth discipleship through religious education and faith-based digital literacy with a broader missional perspective toward the nations. Using a qualitative case study method conducted in a Christian school Mahanaim English Program – English Secondary (MEP–ESP), this research demonstrates how reflective way of purification, guided dialogue, and the use of simple educational media can foster transformative discipleship. The findings show that integrating biblical values within digital realities promotes students’ moral awareness, personal responsibility, and spiritual commitment. Furthermore, faith literacy grounded in the love of Christ provides a foundation for cross-cultural discipleship, preparing youth to live faithfully and influence others in diverse contexts. This article recommends a contextual discipleship model through Christian Religious Education as a practical response to the spiritual needs of the digital generation and as a pathway to engage the nations with the Gospel.